2018
DOI: 10.1002/jobm.201800279
|View full text |Cite
|
Sign up to set email alerts
|

Production and recovery of poly(3‐hydroxybutyrate‐co‐3‐hydroxyvalerate) from biodiesel liquid waste (BLW)

Abstract: Polyhydroxyalkanoates (PHAs) has been paid great attention because of its useful thermoplastic properties and complete degradation in various natural environments. But, at industrial level, the successful commercialization of PHAs is limited by the high production cost due to the expensive carbon source and recovery processes. Pseudomonas mendocina PSU cultured for 72 h in mineral salts medium (MSM) containing 2% (v/v) biodiesel liquid waste (BLW) produced 79.7 wt% poly(3-hydroxybutyrate) (PHB) at 72 h. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…As a fact, PHBV still exhibits a high degree of crystallinity throughout a wide range of compositions from 0 to 95 mol% HV (Cai and Qiu, 2009). Different cultivation strategies have been designed for the incorporation of 3HV monomers in the forming polymeric chain, using organic acid precursors, such as propionic and valeric acid (Zinn et al, 2003;Masood et al, 2012;Follonier et al, 2014;Hilliou et al, 2016;Martla et al, 2018).…”
Section: Poly (3-hydroxybutyrate-co-hydroxyvalerate)mentioning
confidence: 99%
“…As a fact, PHBV still exhibits a high degree of crystallinity throughout a wide range of compositions from 0 to 95 mol% HV (Cai and Qiu, 2009). Different cultivation strategies have been designed for the incorporation of 3HV monomers in the forming polymeric chain, using organic acid precursors, such as propionic and valeric acid (Zinn et al, 2003;Masood et al, 2012;Follonier et al, 2014;Hilliou et al, 2016;Martla et al, 2018).…”
Section: Poly (3-hydroxybutyrate-co-hydroxyvalerate)mentioning
confidence: 99%
“…methane, glucose, fructose), linked to these precursors (Table 2). These studies have confirmed that methanotrophic bacteria, Ralstonia eutropha, Pseudomonas species and Hydrogenophaga pseudoflava were capable to produce only PHB when fed solely with the main substrate (Kim et al 1994;Inn et al 2003;Myung et al 2015;Cal et al 2016;Martla et al 2018) while the specie Ralstonia eutropha DSM 545 was capable to produce PH3HB4HB when fed with sole glycerol (Cavalheiro et al 2012). The addition of precursors led, to PHBV production in all cases investigated.…”
Section: Addition Of 3hv Fraction Precursorsmentioning
confidence: 76%
“…Recently, the archea Haloferax Mediterranei, an extremely halophilic microrganism, has gained a greater attention, due to its faster growth, its high PHBV productivity and its capacity of producing high quality products (Hou et al 2013). Different species of Bacillus, Methilobacterium, Pseudomonas and Rhodospirillacee have been also tested on various substrates (Ueda et al 1992;Smith et al 2008;Zuñiga et al 2013;Martla et al 2018;Balakrishna Pillai et al 2020). Finally, even though less studied if compared to the previous mentioned microorganisms, Alcaligenes, Comamonas, Halomonas and Rhodococcus have been found to be capable to produce PHBV (Choi et al, 2003;Kulkarni et al, 2010;Williams et al, 1994;Zakaria et al, 2013).…”
Section: Phbv Biosynthesis Processes Characteristics and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 181 ] The yield of PHB and PHBV using P. mendocina and mealworms were 55.83 ± 1.53 g L −1 with 88% purity and 37.00 ± 1.81 g L −1 with 89% purity, respectively. [ 183 ] Gram‐negative predator bacterium, Bdellovibrio bacteriovorus HD100, was used for PHA recovery where it attacks by penetrating the membrane and consuming its prey. [ 184 ] It has been reported that B. bacteriovorus HD100 encodes mcl‐ PHA depolymerase ( phaZ Bd ), decreasing the PHA recovery.…”
Section: Recovery Methods Involved In Pha (Downstream Processing)mentioning
confidence: 99%